The effectiveness of electronic discussions on foreign language anxiety levels of adult Egyptian EFL learners - Abul Magd, Dina Amr (AUC Knowledge Fountain, 2015)
This study examines the effect of electronic discussions on adult Egyptian EFL learners’ Foreign Language Anxiety (FLA) levels. It also aims at investigating learners’ perceptions of FLA and the effectiveness of e-discussions with regards to reducing their FLA. Finally, the current study attempts to look into the effect of gender on FLA. For this purpose, a total of 45 learners participated in a pre- and post-online discussion intervention. Students completed the Foreign Language Classroom Anxiety Scale (FLCAS) before and after involvement in the online discussion. Observations also took place before and after the online intervention. Finally, eight participants were interviewed to provide an in-depth analysis of the issue under discussion. Data was analyzed qualitatively and quantitatively to answer the research questions. Findings indicated that e-discussions helped reduce learners’ FLA levels. Furthermore, learners were aware of their FLA, even though their levels of FLA were different. Gender, however, was not found to be a significant variable in the study since there was no significant difference in male and female FLA pre- and post-online discussion. Building on the findings of the study, it is recommended that teachers integrate e-discussions in classes where students suffer from high levels of FLA. Students are also advised to be open to language classes where Computer Assisted Language Learning (CALL) is integrated. Future studies might employ a larger number of participants for more accurate results with regards to gender, as other studies have found gender differences in reported FLA levels.